Dynamics of Bioluminescence Potential and Physical, Bio‐Optical Properties on the Shelf and Shelf‐Slope of Delaware Bay. Issue 9 (9th September 2020) - Shulman, Igor; Penta, Bradley; Anderson, Stephanie; Moline, Mark A.; Oliver, Matthew J.; Cohen, Jonathan H.; Hudson, Katherine
Abstract: The dynamics of physical and bio‐optical properties on the shelf and the shelf‐slope break areas offshore of the Delaware Bay were investigated. Compared to monthly means, there were elevated daily freshwater outflows. Glider observations demonstrated significant changes in bio‐optical properties before and after sampling fresher water masses. Prior to sampling fresher water masses, the glider observations exhibited a coincidence of high values in bioluminescence (BL) potential, chlorophyll, and optical backscattering. However, as the glider started to sample fresher water masses, there was a gradual decoupling of high values in BL potential with the high values in chlorophyll and optical backscattering. This indicates a shift from an autotrophic and mixotrophic toward a more heterotrophic bioluminescent community between water masses. During the glider survey, a high chlorophyll filament was observed by satellite ocean color imagery along the shelf‐slope break of the Delaware Bay. The high chlorophyll filament had weakened and disappeared in satellite imagery over the next 2 days when upwelling was progressing, and the glider started to sample fresher water masses. The filament was on the dense side of the shelf‐slope front, and the glider observations indicated a subduction of high chlorophyll values into subsurface (below the fresher surface water masses) with high values of BL potential deeper than high values of chlorophyll. The studies presented here are the first BL potential studies on the shelf and the shelf slope areas of the Delaware Bay, as well as the first studies of BL potential resulted from deployments of the glider with BL potential sensor on board. Key Points: First studies of bioluminescence potential with the glider deployments on the shelf and the shelf‐slope areas of the Delaware Bay Prior to sampling fresher water, observations show a coincidence of high values in bioluminescence potential and chlorophyll During sampling fresher water, there was a gradual decoupling of high values in bioluminescence potential and chlorophyll